Curing mosquitoes with genetic approaches for malaria control - Kefi, Mary; Cardoso-Jaime, Victor; Saab, Sally A.; Dimopoulos, George (Trends in parasitology, 2024)
A population modification approach involves spreading genes/elements through the populations to make mosquitoes refractory to the parasite.Parasite refractoriness of mosquito vectors can be achieved by genetic manipulations of mosquito endogenous effectors and host factors or by introducing exogenous effectors into the mosquito genome.Gene-drive technology allows the spread and persistence of the desired genes/elements within targeted populations.The success of transgenic mosquitoes in spreading and maintaining desired genes/elements in the field relies on their performance compared with wild types.Field implementation of the transgenic applications is a phase-by-phase process that is subject to public acceptance and regulations. Malaria remains a persistent global public health challenge because of the limitations of current prevention tools. The use of transgenic mosquitoes incapable of transmitting malaria, in conjunction with existing methods, holds promise for achieving elimination of malaria and preventing its reintroduction. In this context, population modification involves the spread of engineered genetic elements through mosquito populations that render them incapable of malaria transmission. Significant progress has been made in this field over the past decade in revealing promising targets, optimizing genetic tools, and facilitating the transition from the laboratory to successful field deployments, which are subject to regulatory scrutiny. This review summarizes recent advances and ongoing challenges in ‘curing’ Anopheles vectors of the malaria parasite. Malaria remains a persistent global public health challenge because of the limitations of current prevention tools. The use of transgenic mosquitoes incapable of transmitting malaria, in conjunction with existing methods, holds promise for achieving elimination of malaria and preventing its reintroduction. In this context, population modification involves the spread of engineered genetic elements through mosquito populations that render them incapable of malaria transmission. Significant progress has been made in this field over the past decade in revealing promising targets, optimizing genetic tools, and facilitating the transition from the laboratory to successful field deployments, which are subject to regulatory scrutiny. This review summarizes recent advances and ongoing challenges in ‘curing’ Anopheles vectors of the malaria parasite.